2021
DOI: 10.1007/s42765-021-00073-z
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Polymer Fibers: Materials, Structures, and Applications

Abstract: Shape memory polymer (SMP) is a kind of material that can sense and respond to the changes of the external environment, and its behavior is similar to the intelligent reflection of life. Electrospinning, as a versatile and feasible technique, has been used to prepare shape memory polymer fibers (SMPFs) and expand their structures. SMPFs show some advanced features and functions in many fields. In this review, we give a comprehensive overview of SMPFs, including materials, fabrication methods, structures, multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 121 publications
0
40
0
Order By: Relevance
“…In two separate studies, short‐chain polyalanine (net points) was introduced into multiblock biopolymers containing poly(ɛ‐caprolactone) segments ( β ‐sheet crystals) via a coupling reaction; nearly complete shape recovery and high shape fixity was observed. [ 123 , 125 ]…”
Section: Other Physical Properties Of the Spider Silk And The Inspire...mentioning
confidence: 99%
See 1 more Smart Citation
“…In two separate studies, short‐chain polyalanine (net points) was introduced into multiblock biopolymers containing poly(ɛ‐caprolactone) segments ( β ‐sheet crystals) via a coupling reaction; nearly complete shape recovery and high shape fixity was observed. [ 123 , 125 ]…”
Section: Other Physical Properties Of the Spider Silk And The Inspire...mentioning
confidence: 99%
“…In two separate studies, short-chain polyalanine (net points) was introduced into multiblock biopolymers containing poly(ɛ-caprolactone) segments (𝛽-sheet crystals) via a coupling reaction; nearly complete shape recovery and high shape fixity was observed. [123,125] The hybrid silk material fabricated by introducing silk fibroin into poly(vinyl alcohol) (PVA), has a two-way shape-memory effect because of the competitive H-bonds between silk fibroin and PVA from water as a switch, the 𝛽-sheet structure as net points, and the swelling plasticizing effect of its asymmetric laminated structure. [124b] Polyurethanes contain soft and hard segments, which are similar to the crystalline and amorphous regions of spider silk.…”
Section: Artificial Fibers Exhibiting Torsional Energy Dissipation An...mentioning
confidence: 99%
“…These intelligent smart materials have been extensively studied for biomedical, textile, aerospace, civil infrastructure and structural engineering applications to date. [7][8][9][10][11] By applying an external load at a temperature higher than the glass transition temperature (T g ), a thermally induced SMP material is programmed to the desired shape. The material is then cooled until it turns into a frozen polymer at a low temperature, while the programmed shape remains fixed.…”
Section: Introductionmentioning
confidence: 99%
“…SMPs and SMPCs have a wide range of applications, from micro‐scale to large‐scale engineering. These intelligent smart materials have been extensively studied for biomedical, textile, aerospace, civil infrastructure and structural engineering applications to date 7–11 …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the primary purposes or service demands of textile materials have also changed imperceptibly from the aspects of covering, warmth preservation, protection, beauty, security, comfort, health, interaction, and intelligence. On these grounds, it can be found that with the advances of Internetof-Things and artificial intelligences, textile materials are no longer limited to the traditional functions of protection, warm-keeping, and aesthetic, but should be given more smart or intelligent attributes, such as energy harvesting, [1][2][3] energy storage, [4,5] autonomous response, [6,7] information interaction, [8,9] data transmission, [10,11] light emitting, [12,13] color changing, [14] shape memory, [15] thermal regulation, [16,17] selfhealing, [18a] self-adaption, [19] etc. In addition, considering that human oriented wearable electronics will be highly integrated and miniaturized, completely safe and comfortable, and fully portable in the future, it is also expected to design various functional electronics directly into textile structures, such as fibers, yarns or fabrics.…”
mentioning
confidence: 99%